Innovation, Research and Development Management - Gilbert, Patrick; Bobadilla, Natalia; Gastaldi, Lise; Le Boulaire, Martine; Lelebina, Olga (Wiley-ISTE, 2018)
In today's business environment, as organizations constantly seek to growth and develop through the optimization of their innovative and creative potential, understanding the critical issues and management practices in R & D is essential. This book provides a critical revaluation of the state of the art issues and concepts in R & D management. The views expressed are those of leading French researchers and professionals in this field, fed by empirical studies in national and international firms.